NCOG-21. INTERIM RESULTS OF THREE COGNITIVE REHABILITATION STRATEGIES IN PATIENTS WITH LOWER GRADE GLIOMAS. (9th November 2020) - Taylor, Jennie; Weyer-Jamora, Christina; Brie, Melissa; Bracci, Paige; Smith, Ellen; Luks, Tracy; Braunstein, Steve; Villanueva-Meyer, Javier; Gehring, Karin; Aguilera, Adrian; Bush, Nancy Ann Oberheim; Clarke, Jennifer; et al.
Abstract: BACKGROUND: Patients with lower grade (2 and 3) gliomas (LrGG) are living longer, but often with cognitive impairments from their tumor and treatments. However, cognitive assessments and access to cognitive rehabilitation are not a standard part of care. We present preliminary results of a pilot study investigating feasibility and efficacy of three cognitive rehabilitation strategies for stable LrGG patients – in-person manualized cognitive rehabilitation; iPad based cognitive rehabilitation program of retraining and compensation strategies (ReMind); or daily instructional text messages (Healthy SMS). METHODS: Eligible patients were adults with clinically and radiologically stable LrGG, > 6 months from last treatment, and ≥1 standard deviation (SD) below normal on ≥ 2 domains of neuropsychological assessments. Patients were first offered in-person cognitive rehabilitation or randomized to ReMind or Healthy SMS if unable to attend in-person. Interventions lasted 3 months. Neuropsychological and HRQOL assessments, using PROMIS NeuroQOL, were conducted at baseline, 3, and 6 months post-intervention. Feasibility was defined as attending ≥80% of in-person sessions; completing ≥80% of ReMind tasks; or not opting out of Healthy SMS texts. RESULTS: To date 23/60 patients have enrolled: 11 in-person and 12 randomized to ReMind (5) or Healthy SMS (7). Demographic and clinical characteristics were similar between cohorts. Median age at testing was 46 years, with 65% female, and 78% having received prior radiation (median 4.1 years, range 3.2 – 11.5). At baseline, processing speed was the most common domain of impairment with 43% ≥ 1.5 SD below normal and 36% patients reporting subjective cognitive impairment on HROQL assessment. Feasibility was 71% for in-person rehabilitation; 50% for ReMind; and 100% for Health SMS. CONCLUSION: These preliminary results demonstrate that stable LrGG patients with subjective and objective cognitive impairments can reasonably engage in cognitive rehabilitation interventions. Updated data including post-intervention neuropsychological and HROQL related changes will be presented.